Hazard and Risk Analysis for Ring Spinning Yarn Production Process by Integrated FTA-FMEA Approach - Mutlu, Nazli Gulum; Altuntas, Serkan (EGE UNIV, 2019)
The hazard analysis and management is vital in textile industry to avoid losing customers and wasting resources caused by the failures in production systems. Risk analysis is also very significant to decrease possible hazards and to avoid possible damage in production systems. In this study, an approach based on Failure Mode and Effects Analysis (FMEA) and Fault Tree Analysis (FTA) is proposed to analyze the ring spinning yarn production process in a textile industry. First, the possible hazards in the production line, yarn production system, in an integrated company operating in the textile sector are analyzed by FTA method. Then, FMEA is applied to ring spinning yarn production process in a textile industry to rank all possible risks corresponding to hazards in descending order with respect to both occupational health and safety. It is very important to remove all possible hazards in textile industry to decrease the number of risks related to occupational health and safety. Therefore, in total of 57 hazard root causes are determined in the yarn production department. Subsequently, the faults related to the hazard root causes are examined by FTA and then risk corresponding to these hazards are prioritized by FMEA. The results obtained from the proposed FTA-FMEA approach show that decision makers and engineers can easily decrease the number of hazards and risks with respect to both occupational health and safety in practice.
Keywords: FMEA; FTA; Risk and hazard analysis; Production system; Ring spinning yarn; Textile industry; KNITTED FABRIC PROPERTIES; FAILURE; SAFETY; QUALITY; COMPACT; Materials Science